Social Justice Adult EducationComparative Perspectives from Poland and the United States - Susan M. Yelich Biniecki; Marzanna Pogorzelska (Adult Education Research Conference, 2015)
This paper examines and compares how social justice adult education currently is situated within two nation statesPoland and United States. Vocabulary, conceptual frameworks, and several themes are compared. The discussion broadens our understanding of how social justice education is positioned within two, complex socio-cultural contexts and suggests implications for practice.
Keywords: Social justice; international education; Poland; United States